PENGARUH RASIO PELARUT DAN WAKTU PENGENDAPAN PADA ISOLASI INULIN UBI JALAR (Ipomoea batatas) - Bara Yudhistira; Siswanti Siswanti; Dea Anindita W (AGROINTEK, 2020)
Inulin is one of many functional food components that becomes a trend nowadays. Inulin can be found in the stems and roots/tubers of plants. Yellow sweet potato (Ipomea batatas L.) is a widespread species of sweet potato with abundant availabilty in Indonesia, where it is exploited only as a source of carbohydrate. From the previous study, it was stated that sweet potato can be used as an alternative resource of inulin besides dahlia and Dioscorea spp. tubers. This study aimed at extracting and isolating inulin from aqueous extract of yellow sweet potato with 3 different ratio (1:1, 1:2, 1:3) and 3 different time (6, 12, 18 hours) to determine its effect on the yield of inulin. After preparation of extracts, crude inulin was precipitated in 96% ethanol. The free reducing sugar from sweet potato flour was tested using Dinitrosalisylic Acid Method (DNS). After precipitation, inulin powder was obtained by an overnight drying process using oven at 60ºC and characterized by color, solubility, water absorption, moisture content and ash content. Its inulin structure was analyzed and confirmed by Fourier Transformed Infrared (FT-IR) spectroscopy. The results showed that different ethanol ratio and precipitating time has effect on the yield of inulin. The highest yield of inulin were 8.80% obtained from solvent ratio 1:3 with 18 hours of precipitating time. It can be concluded that yield of inulin were affected by solvent ratio, precipitating time and degree of polymerization (DP). Higher solvent ratio and precipitating time could obtain higher yield of inulin.